2016
DOI: 10.1038/boneres.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Mice with a heterozygous Lrp6 deletion have impaired fracture healing

Abstract: Bone fracture non-unions, the failure of a fracture to heal, occur in 10%–20% of fractures and are a costly and debilitating clinical problem. The Wnt/β-catenin pathway is critical in bone development and fracture healing. Polymorphisms of linking low-density lipoprotein receptor-related protein 6 (LRP6), a Wnt-binding receptor, have been associated with decreased bone mineral density and fragility fractures, although this remains controversial. Mice with a homozygous deletion of Lrp6 have severe skeletal abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Two images were averaged per frame (Bouxsein et al, 2010). Following scanning, the binarized images were used to calculate several three-dimensional bone healing parameters as detailed previously (Burgers et al, 2016, Komatsu et al., 2010). In brief, tissue volume (TV) generated by NRecon delineates tissue from non-tissue, which we defined as the callus volume.…”
Section: Methodsmentioning
confidence: 99%
“…Two images were averaged per frame (Bouxsein et al, 2010). Following scanning, the binarized images were used to calculate several three-dimensional bone healing parameters as detailed previously (Burgers et al, 2016, Komatsu et al., 2010). In brief, tissue volume (TV) generated by NRecon delineates tissue from non-tissue, which we defined as the callus volume.…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies, in which the β-catenin signaling was either inhibited or activated in chondrocytes, osteoblasts, or osteocytes, demonstrated that activation of β-catenin signaling promotes osteoblast differentiation and bone formation and inhibition of osteoclast formation and bone resorption. [1][2][3][4][5][6][7] However, the detailed mechanisms of how postnatal bone growth and bone remodeling are regulated by β-catenin signaling remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, LRP5 À/À mice, LRP6 À/+ mice and mice overexpressing the LRP5/6-antagonist Kremen2 showed reduced bone formation and mechanical stability of the fracture callus. (12,13) By contrast, mice lacking Wnt inhibitors such as sclerostin and midkine or overexpressing Wnt agonists such as Wnt7b displayed accelerated fracture healing. (14)(15)(16)(17) Wnt3 has been extensively studied as a therapeutic option and might be a promising candidate.…”
Section: Introductionmentioning
confidence: 99%